Detecting sexually antagonistic coevolution with population crosses - Rowe, Locke; Cameron, Erin; Day, Troy (Proceedings of the Royal Society B : Biological Sciences, 2003)
The result of population crosses on traits such as mating rate, oviposition rate and survivorship are increasingly used to distinguish between modes of coevolution between the sexes. Two key hypotheses, erected from a verbal theory of sexually antagonistic coevolution, have been the subject of several recent tests. First, statistical interactions arising in population crosses are suggested to be indicative of a complex signal/receiver system. In the case of oviposition rates, an interaction between populations (x, y and z) would be indicated by the rank order of female oviposition rates achieved by x, y and z males changing depending upon the female (x, y or z) with which they mated. Second, under sexually antagonistic coevolution females will do 'best' when mated with their own males, where best is defined by the weakest response to the signal and the highest fitness. We test these hypotheses by crossing strains generated from a formal model of sexually antagonistic coevolution. Strains differ in the strength of natural selection acting on male and female traits. In our model, we assume sexually antagonistic coevolution of a single male signal and female receptor. The female receptor is treated as a preference function where both the slope and intercept of the function can evolve. Our results suggest that neither prediction is consistently supported. Interactions are not diagnostic of complex signal-receiver systems, and even under sexually antagonistic coevolution, females may do better mating with males of strains other than their own. These results suggest a reinterpretation of several recent experiments and have important implications for developing theories of speciation when sexually antagonistic coevolution is involved.